Novel STMN2 Variant Linked to Amyotrophic Lateral Sclerosis Risk and Clinical Phenotype - Theunissen, Frances; Anderton, Ryan S.; Mastaglia, Frank L.; Flynn, Loren L.; Winter, Samantha J.; James, Ian; Bedlack, Richard; Hodgetts, Stuart; Fletcher, Sue; Wilton, Steve D.; Laing, Nigel G.; MacShane, Mandi; et al. (Frontiers in Aging Neuroscience, 2021)
Objective There is a critical need to establish genetic markers that explain the complex phenotypes and pathogenicity of ALS. This study identified a polymorphism in the Stathmin-2 gene and investigated its association with sporadic ALS (sALS) disease risk, age-of onset and survival duration. Methods The candidate CA repeat was systematically analyzed using PCR, Sanger sequencing and high throughput capillary separation for genotyping. Stathmin-2 expression was investigated using RT-PCR in patient olfactory neurosphere-derived (ONS) cells and RNA sequencing in laser-captured spinal motor neurons. Results In a case-control analysis of a combined North American sALS cohort (n = 321) and population control group (n = 332), long/long CA genotypes were significantly associated with disease risk (p = 0.042), and most strongly when one allele was a 24 CA repeat (p = 0.0023). In addition, longer CA allele length was associated with earlier age-of-onset (p = 0.039), and shorter survival duration in bulbar-onset cases (p = 0.006). In an Australian longitudinal sALS cohort (n = 67), ALS functional rating scale scores were significantly lower in carriers of the long/long genotype (p = 0.034). Stathmin-2 mRNA expression was reduced in sporadic patient ONS cells. Additionally, sALS patients and controls exhibited variable expression of Stathmin-2 mRNA according to CA genotype in laser-captured spinal motor neurons. Conclusions We report a novel non-coding CA repeat in Stathmin-2 which is associated with sALS disease risk and has disease modifying effects. The potential value of this variant as a disease marker and tool for cohort enrichment in clinical trials warrants further investigation.